Global DNA hypomethylation occurs in the early stages of intestinal type gastric carcinoma. Issue 3 (September 1996) - Cravo, M; Pinto, R; Fidalgo, P; Chaves, P; Glória, L; Nobre-Leitão, C; Costa Mira, F
Abstract : BACKGROUND: Global DNA hypomethylation has been found in the premalignant stages of some neoplasms and has been implicated as an important factor for tumour progression. AIMS: The aim of this study was to evaluate whether DNA hypomethylation occurs during the process of gastric carcinogenesis. METHODS: Gastric specimens were obtained from 49 patients and histologically classified as: normal 10, superficial gastritis 14, chronic atrophic gastritis with intestinal metaplasia 15, and intestinal type of gastric carcinoma 10. Global DNA methylation was assessed by incubating DNA with (3H)-S-adenosylmethionine and Sss1 methylase. A higher incorporation of (3H) methyl groups reflects a lower degree of intrinsic methylation. RESULTS: A graduated increase in (3H) methyl group incorporation into DNA was found over the range extending from normal gastric mucosa, to superficial gastritis and to chronic atrophic gastritis (136, 556 (24, 085) v 235, 725 (38, 636) v 400, 998 (26, 747 dpm/micrograms/DNA respectively; p = 0.0002). No further increase was found in specimens from patients with carcinoma. No differences were found between extent of DNA methylation in neoplastic or non-neoplastic mucosa from patients with gastric carcinoma. Hypomethylation of DNA increased substantially with severe atrophy (p = 0.01) or with type III intestinal metaplasia (p = 0.15). CONCLUSIONS: Global DNA hypomethylation occurs in the early stages of gastric carcinogenesis, and it may be a novel biomarker of gastric neoplasia, useful in monitoring the response to chemopreventive agents.